The impact of a PERMA model-based positive psychology intervention on fear of recurrence of inflammatory bowel disease: a randomized controlled trial - Qian, Yuanyuan; Ma, Linlin; Hao, Jianru; Zhang, Lu; Liu, Ying; Xu, Yongping; Dai, Lifen; Luo, Yanfang; Su, Zhenzhen (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the effects of a positive psychological intervention based on the PERMA model on fear of recurrence, subjective well-being, psychological resilience, and quality of life in patients with inflammatory bowel disease (IBD).MethodsThis study was conducted as a single-blind, two-arm randomized controlled trial at Jiangnan University Affiliated Hospital from May to July 2024. A total of 93 hospitalized patients experiencing fear of recurrence related to IBD were randomly assigned to either the intervention group (n = 47) or the control group (n = 46). Patients in the intervention group received positive psychological intervention based on PERMA model, while patients in the control group received standard nursing. The levels of fear of recurrence, subjective well-being, resilience, and quality of life were assessed at baseline (T0), day of discharge (T1), 2 weeks post-discharge (T2), 4 weeks post-discharge (T3), and 8 weeks post-discharge (T4). Data were analyzed using independent sample t-tests, chi-square tests, and generalized estimating equations (GEE).ResultsResilience and quality of life scores at T2 were significantly higher in the intervention group than in the control group. As the duration of the intervention increased, there was a significant decrease in the level of fear of recurrence (T3: U = −1.978, p = 0.048; T4: U = −2.116, p = 0.034), alongside improvements in subjective well-being (T3: t = 2.731, p = 0.008; T4: t = 3.490, p < 0.001), psychological resilience (T3: t = 4.824, p < 0.001; T4: t = 5.699, p < 0.001), and quality of life (T3: U = −2.576, p = 0.010; T4: U = −2.746, p = 0.006), all of which were statistically significant. Furthermore, a significant group-related shift was noted in psychological resilience (χ2 = 14.353, p < 0.001). Notably, the effects of time and interaction on fear of recurrence, subjective well-being, psychological resilience, and quality of life were statistically significant (all p < 0.05).ConclusionPositive psychological interventions based on the PERMA model significantly reduced fear of recurrence in IBD patients, and positively affected their subjective well-being, psychological resilience, and quality of life.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=230313 ChiCTR2400085278.